PARADIGMA STRUCTURE CONDUCT AND PERFORMANCE VERSUS HIPOTESIS EFISIENSI: MANAKAH YANG MENCERMINKAN INDUSTRI PERBANKAN INDONESIA - Pracoyo Budi Jatmiko (UGM, 2000)
There are two competing hyphotesis with regard to market structure and performance. The first hypothesis is structure-conduct-performance paradigm which emphasized on market collusion ad the second hypothesis is efficiency hyphotesis which emphasized on market collusion and the second hyphotesis with respect to the Indonesian banking industry using pooling data from 16 largest bank for period 1988-1995. The results were suprisingly support the efficiency hyphotesis. It means that government regulation has succesfully fostered banks to enhance their efficiency and then improved their profit. However, raders have to use the finding prudently because there is a fw sample limitation.